TATHWIR AL LU’BAH “BRAIN’S ADVENTURE” LI TANMIYATI DZAKIROH QOSHIROTUL MADAY LADAY THULLAB FI TA’LIM ALAROBIYYAH - Lailatul Qomariyah; Isniyatun Niswah Mz; Abdul Qodir; Mu’at Mu’at; Iva Inyatul Ilahiyah; Luthfi Hakim; Nur Kuswanti (Universitas Islam Negeri Mataram, 2024)
It turns out that the phenomenon in teaching Arabic is that students' thinking skills are still low. This phenomenon is evident in the number of students who give wrong answers to Arabic language questions that require deep thinking during Arabic language teaching. This is not consistent with the current curriculum that requires students to develop their mentality, specifically to think either critically or creatively. This phenomenon indicates that the level of thinking skills, especially in short-term memory, among students is still low. Therefore, the aim of this research is to develop the game